Ewa Radanowicz (2020). W szkole wcale nie chodzi o szkołę(ang. At school it is not at all about school), ss. 296, Wydawnictwo SENSOR Justyna Radanowicz (Przegląd Pedagogiczny, 2025)
Recenzja publikacji: Ewa Radanowicz (2020). W szkole wcale nie chodzi o szkołę(ang. At school it is not at all about school), ss. 296, Wydawnictwo SENSOR Justyna Radanowicz.